P14.61 Tumor Treating Fields (TTFields) combined with lomustine (CCNU) and temozolomide (TMZ) in newly diagnosed glioblastoma (GBM) patients - a bi-centric analysis. (6th September 2019) - Lazaridis, L; Schäfer, N; Schmidt, T; Stoppek, A; Weller, J; Tzaridis, T; Scheffler, B; Pierscianek, D; Kleinschnitz, C; Stuschke, M; Sure, U; Herrlinger, U; et al.
Abstract: BACKGROUND: TTFields combined with TMZ demonstrated significantly improved PFS, OS and long-term survival in newly diagnosed glioblastoma (ndGBM) patients, compared to TMZ monotherapy in the EF-14 trial; independent of MGMT-promotor methylation-status, age, grade of resection and performance status. Recently, improved efficacy of lomustine (CCNU)/TMZ compared to TMZ monotherapy in ndGBM patients with MGMT-promotor methylation was reported in the CeTeG trial (NOA-09). Taken into account that TTFields showed a strong safety profile as well as a high potential being combined with other modalities and the very encouraging results for methylated MGMT-promotor GBM patients in the CeTeG trial, there is a strong rationale in combining these treatment regimens. Here, we present a case series of patients receiving a combination of both modalities, TTFields and CCNU/TMZ. METHODS: Patients with ndGBM and MGMT-promotor methylation underwent a combined therapy of TTFields plus CCNU/TMZ after surgery and radiochemotherapy. Safety, feasibility as well as first efficacy results of this combined therapy are reported at data cut-off (31.12.2018). Most recent data, including compliance to TTFields therapy, will be presented at the EANO annual meeting. RESULTS: Twelve patients with MGMT-promotor methylated ndGBM (median, range: age 49.5, 26–69; KPS 90, 60–100) have been treated with a combination of TTFields plus CCNU/TMZ. The analysis included patients with complete resection (n=6), partial resection (n=5) as well as biopsy (n=1). CTCAE grade 3 hematotoxicities were observed in six patients, but were not considered to be related to the addition of TTFields to lomustine/TMZ. Medical device site reactions (low-grade skin reactions) were detected in five patients. At data cut-off, the analyzed patient population demonstrated a median PFS of 18.7 months, whereas the median OS was not yet reached. CONCLUSION: The results of this analysis provide first indication that the combination of TTFields/lomustine/TMZ is safe and feasible. Moreover, the observed survival outcomes point to preliminary beneficial effects of the triple combination. Additional follow-up and a higher sample size is required and planned for further toxicity analysis and efficacy assessment of this combination.